Philosophical hermeneutics as theoretical background of bioethics: Elements for a critical assessment - Pessina, Adriano (Medicina e Morale, 1996)
The article examines the relationship between philosophical hermeneutics and bioethics, though a critical essay on Hans Georg Gadamer's theses on this subject, and argues about the question of what the epistemological statue of bioethics is. In fact the author considers that the variety of research for the theoretical settings of bioethics which many scholars - above all those with a biomedical training - try in order to provide an evaluation which is in harmony with the concrete operative requirements urged by scientific progress only reveals a situation of the epistemological "fluidity" of bioethics. This situation is emphasized by the long lasting crisis of the models of western rationality which involves both scientific and the philosophical disciplines. The hermeneutical perspective intends to demonstrate that: 1. the fluidity and the historicity of evaluations and of the intervention procedures is an insuperable condition; 2. the fusion between the act of comprehension and the moment of application is necessary. Then, the justification of bioethics as "episteme" passes through the confutation of the reductive claims of hermeneiutics. In fact the article supports the legitimacy of bioethics, not only at a practical evaluation level but also at a theoretical-normative level.